Flash Learning Games Wow Students and Instructors: Moving Toward An Academic Gaming Portal - Dan H Lim (Journal of Systemics, Cybernetics and Informatics, 2003)

(untitled)
This paper describes and discusses the rationale, background, design, and implementation of Flash learning games. The paper explains why Macromedia Flash has been selected as the authoring tool in the development of highly interactive learning games for online learning. The background evolutionary process of developing the learning games points out why it has been a daunting task to create compelling learning games that impact learning. Designing learning game objects that allow other educators to customize game content is the core of this paper. The author envisions this academic gaming project will evolve into an academic gaming portal, developed in conjunction with other major institutional partners.